Republic of Belarus : Financial Sector Assessment Program; Technical Note; Deposit Insurance. (IMF Staff Country Reports; Country Report ;, 2006)
This technical note on deposit insurance on the Republic of Belarus explains the status of the deposit insurance system. The current system of deposit insurance is governed by two different pieces of legislation, each in turn elaborated by a separate National Bank of Belarus (NBB) resolution. Reforming a deposit insurance scheme raises the issue of how to achieve a nondisruptive transition. Independently of whether Belarus chooses to follow a step approach or provide coverage while it reforms its banking system, it will be essential to address the current liquidity shortage.